Becoming Soviet Jews : The Bolshevik Experiment in Minsk - Bemporad, Elissa (Modern Jewish experience (Bloomington, Ind.), 2013)
"Recasting our understanding of Soviet Jewish history, Becoming Soviet Jews demonstrates that the often violent social changes enforced by the communist project did not destroy continuities with prerevolutionary forms of Jewish life in Minsk. Using Minsk as a case study of the Sovietization of Jews in the former Pale of Settelment, Elissa Bemporad reveals the ways in which many Jews acculturated to Soviet society in the 1920s and 1930s while remaining committed to older patterns of Jewish identity, such as Yiddish culture and education, attachment to the traditions of the Jewish workers' Bund, circumcision, and kosher slaughter. This pioneering study also illuminates the reshaping of gender relations on the Jewish street and explores Jewish everyday life and identity during the years of the Great Terror"--From the publisher.